Building Human Resources Characteristics in Public Services: A Phenomenological Study on Civil Servants - Muniroh, Muniroh; Pawenary, Pawenary (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to understand, analyze and describe the focus of Building Characteristics of State Civil Apparatus Employees in carrying out their duties and functions as public service lecturers - state servants who are required to serve student learning, research and community service in university and government environments. The method used by the researcher in this study is a Qualitative method with a Phenomenological Study approach. The data collection technique is based on secondary data processes, namely books, scientific journals, laws and regulations and seminar results as well as empirical data, namely; through the process of observation and interviews. The research informants are Academic Staff, Students and Lecturers of State Civil Apparatus Employees at Esa Unggul University and Lecturers at government higher education institutions.The results of the study found by the researcher, that